ZIRCONIUM ABUNDANCES IN THE CENTRAL PART OF THE dSph FORNAX GALAXY - Andrievsky, S. M.; Korotin, S. A.; Hill, V.; Zhukova, A. V. (Одеські астрономічні публікації, 2017)
We derived LTE zirconium abundance in a sample of 81 giant stars in dwarf spheroidal Fornax galaxy. The LTE synthesis was used for this aim. We obtained the lower Zr abundance in Fornax galaxy comparing to the relevant value in the thick/thin disc of the Milky Way. We note that this result may be aﬀected by the NLTE eﬀects that decrease the real zirconium abundance.